Analisis Hasil Belajar IPS Siswa Sekolah Dasar berdasarkan Motivasi Belajar - Budiharti, Ulan Sapitri; Nurhayati; Anitra, Rien (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2024)
This study analyzes the relationship between learning motivation and student achievement in Social Studies. The research employed a descriptive quantitative method with a sample of 24 students. Data were collected through a motivation questionnaire and analyzed using descriptive statistics and simple correlation to identify the relationship between learning motivation and student achievement. The findings indicate that most students have moderate to low learning motivation, which aligns with their academic performance, which also falls within the moderate category. A positive correlation was found between learning motivation and student achievement, where students with higher motivation tend to achieve better results. The study recommends implementing more interactive and engaging teaching methods to enhance learning motivation and learning outcomes.